The Effect Of Substituting Butterfly Pea Extract As A Natural Dye In Mochi Production - Fikkra, Kaffaka Likka; Holinesti, Rahmi (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
Mochi is a traditional Japanese food made from glutinous rice flour with a sweet taste and a distinctive soft texture that turns chewy when eaten. Mochi is typically round in shape, filled with peanut paste, and coated with roasted cornstarch. In Indonesia, mochi has various variations, one of which involves modifying the mochi's outer layer by adding food coloring to the dough. As time progresses, people have become more aware of the negative effects of synthetic ingredients, leading consumers to shift towards using natural food colorings. Butterfly pea flowers are one alternative source of natural food coloring. These flowers contain anthocyanin compounds that can produce a blue color. The use of butterfly pea flowers does not affect the taste of food products since it only contains anthocyanins. The purpose of this study is to analyze the quality of mochi with the addition of butterfly pea flower extract. The research method employed is a pure experiment, using a Completely Randomized Design (CRD) with three repetitions. Data was collected by surveying a limited group of panelists, who are Family Welfare Science lecturers with a concentration in Culinary Arts at the Faculty of Tourism and Hospitality, Universitas Negeri Padang. Data was analyzed using Analysis of Variance (ANOVA), and if F-value > F-table, then the Duncan test was conducted. The research results indicate a significant effect on color quality. However, the shape (neat and uniform), aroma, texture, and taste did not show a significant effect. The highest overall scores were as follows: neat shape 3.11 (X1), uniform shape 3.11 (X1), blue color 3.44 (X1), pleasant aroma 3.33 (X0), chewy texture 3.67 (X1), and sweet taste 3.33 (X1). The best result in this study was treatment (X1) with a 50% substitution of butterfly pea flower extract.